KOMPARASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN ANALYTICAL HIERARCY PROCESS (AHP) UNTUK PEMILIHAN STAF LABORATORIUM KOMPUTER STMIK WIDYA CIPTA DHARMA SAMARINDA - Salmon -; Bartolomius Harpad (BPSDMP Kominfo Manado, 2018)
The main tasks of the computer laboratory staff are: practical administration services, preparation ofpracticum, recruitment and guidance of computer lab assistants, monitoring and supervising theimplementation of practicum and practice test. Selection of laboratory staff at this time made only directappointment by the leadership so the performance of staff is not good because the selected staff not inaccordance with the expertise it has. From these problems will be raised research Comparative Method ofSimple Additive Weighting (SAW) and Analytical Hierarcy Process (AHP) For Selection of ComputerLaboratory Staff In STMIK Widya Cipta Dharma Samarinda. The comparative results resulting from theSimple Additive Weighting (SAW) method and the Analytical Hierartical Process (AHP) method recommendthe appropriate Analytical Hierartical Process (AHP) method in the Selection of laboratory staff, where theAnalytical Hierarchical Process (AHP) method is considered appropriate to represent natural thinking tendto group system elements to different levels of each level containing similar elements so it is better to use forthe selection of laboratory staff that involves many criteria with different hierarchy levels. In addition, the32AHP method also provides measurement scales and methods to get priority for all hierarchy criteria, sinceeach criterion has unequal priorities.Keyword :Comparative, Simple Additive Weighting (SAW), Analytical Hierarchy Process (AHP),ComputerLaboratory Staff Selection.